E(x)=2×(x+3)²-(2+x)(x-2)-2(5x+7)-7 aratati ca E(√3-1)=3
PLSSS!!​


Răspuns :

Răspuns:

cred ca ai gresuit cand ai copiat, atât mi-a dat mie

Explicație:

(x+3)^2=[tex]x^{2}[/tex]+6x+9

-(2+x)(x-2)= -(2+x)(2-x)= - (4-[tex]x^{2}[/tex])= -4 +[tex]x^{2}[/tex]

-2(5x+7)= -10x-14

2[tex]x^{2}[/tex]+12x+18-4+[tex]x^{2}[/tex]-10x-14-7= 3[tex]x^{2}[/tex]+2x-7

E([tex]\sqrt{3}[/tex]-1)= 3x([tex]\sqrt{3}[/tex]-1)^2+2[tex]\sqrt{3}[/tex]-2-7=3x(3-2[tex]\sqrt{3}[/tex]+1)+2[tex]\sqrt{3}[/tex]-9=9-6[tex]\sqrt{3}[/tex]+2[tex]\sqrt{3}[/tex]-9= -4[tex]\sqrt{3}[/tex]